Developing a New Instrument for Assessing Acceptance of Change - Di Fabio, Annamaria; Gori, Alessio (Frontiers in Psychology, 2016)
This article focuses on the usefulness of going beyond the concept of resistance to change and capitalizing on the use of a model that includes positivity and acceptance of change. We first discuss the theoretical background of this new construct in the work and organizational fields and then evaluate the psychometric properties of a new measure for assessing acceptance of change. The results of exploratory factor analysis indicated a factor structure with five principal dimensions; besides confirmatory factor analysis goodness of fit indices indicated a good fit of the model to the data. All the dimensions showed good values of internal consistency. The results of the present study indicate that the Acceptance of Change Scale is a brief and easily administered instrument with good psychometric properties that can promote the development of clients’ strengths and the growth of a sense of Self, thereby helping them choose their own way without losing any opportunities in their lives and their work.